Investigation on the correlation between eye movement and reaction time under mental fatigue influence - Renata, Vianney (2018)
This study attempts to understand to which extent the eye behavior is relatable with human’s mental chronometry in responding to changes subjected to different levels of mental fatigue. With the recent development of eye tracking technology, research in eye movement and pattern has increased due to its potential to be a non-obstructive physiological measure tool. An analysis of the eye movement metrics when interacting with multiple short performance-based tasks under different states of mental fatigue is performed. It is concluded that the eye movement has influence in the resulting reaction time and the mental fatigue state of the individual. Thus, indicating the relationship as a strong potential to predict an individual’s mental fatigue state. Another finding is that the relationship between the eye movement metrics and mental chronometry becomes stronger as the subjective mental fatigue level increases.